(untitled) (Comprehensive Journal of Science, 2025)
This cross-sectional study aimed to determine the prevalence and distribution of antinuclear antibody (ANA) levels among patients referred for laboratory testing at a specialized medical laboratory in Al-Bayda, Libya, during 2024-2025. A retrospective analysis of 244 patient records was conducted, examining age, sex, test year, and ANA results (categorized as normal or elevated). The findings revealed that the overwhelming majority of tested individuals (92.2%) exhibited ANA levels within normal reference ranges, while only a small subset (7.8%) showed elevated levels. The study population demonstrated a mean age of 42.3 years with a notable female predominance (71.7%). Among the 19 positive cases, females showed higher positivity rates (9.1%) compared to males (4.3%), and individuals aged ≥40 years constituted 63% of positive results. However, statistical analysis indicated no significant associations between ANA positivity and sex (χ² = 2.15, p = 0.14) or age (t = 1.32, p = 0.19). The observed ANA positivity rate (7.8%) was notably lower than rates reported from other Libyan cities (9-11%) and international benchmarks. These findings highlight the need for expanded multicenter studies across Libya to better understand regional variations in autoimmune disease prevalence and improve diagnostic capabilities